Mentorship Programme Criteria and Performance Outcomes of Nurses’ Perceptions - Rudin, Noriedayu MN; Ludin, Salizar M (UI Scholars Hub, 2018)
Background: Mentoring of new staff nurses is a common practice, and international studies have shown it to be associated with increased retention rates, better acquisition of nursing professional identity and increased job satisfaction. However, the outcomes of mentoring programmes in Malaysia are unclear, and in this study, we aimed to explore them. Methods: A cross-sectional study was conducted via convenience sampling at two hospitals. A Mentoring Novice for Medical Surgical Nurse (MNMSN) questionnaire was distributed to recent graduates/full-time nurses. It consisted of 50 items pertaining to the assessment of patient, clinical decision making, cultural competency, commitment to professional nursing standards, positive feeling about nursing at this hospital and willingness to remain in the nursing profession. Results: A total of 61 nurses responded (response rate 100%). Significant differences pre- and post-mentorship programme were observed (patient assessment r = 0.304, p = 0.009; clinical decision-making r = 0.394, p = 0.006; cultural competency r = 0.202, p = 0.01; commitment to professional nursing standards r = 0.423, p = 0; positive feeling about nursing at this hospital r = 0.404, p = 0.001; and willingness to remain in the nursing profession r = 0.312, p = 0.007). Conclusion: The mentorship programme had a positive impact on the clinical component of nursing among hospital-based nurses.